2011
DOI: 10.1097/ccm.0b013e318206d285
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 and angiopoietin-2 as clinically informative prognostic biomarkers of morbidity and mortality in severe sepsis*

Abstract: Angiopoietin-1 levels at admission and both angiopoietin-1 and angiopoietin-2 levels measured serially correlated with 28-day mortality in severe sepsis. Angiopoietin-2 levels also correlated with organ dysfunction/injury and a validated clinical sepsis score. These results suggest the use of angiopoietins as clinically informative biomarkers of disease severity and patient outcome in severe sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
154
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(172 citation statements)
references
References 45 publications
11
154
3
3
Order By: Relevance
“…Recently, Ricciuto et al (2011) confirmed, in their study with 70 patients, the predictive power of Ang-1 and -2 as prognostic marker in the course of sepsis. Ang-1 plasma levels at admission and during the course of disease, both Ang-1 and -2 highly correlated with 28-day mortality in severe sepsis.…”
Section: Ang-1 and -2mentioning
confidence: 51%
“…Recently, Ricciuto et al (2011) confirmed, in their study with 70 patients, the predictive power of Ang-1 and -2 as prognostic marker in the course of sepsis. Ang-1 plasma levels at admission and during the course of disease, both Ang-1 and -2 highly correlated with 28-day mortality in severe sepsis.…”
Section: Ang-1 and -2mentioning
confidence: 51%
“…Regarding their antagonistic roles, especially the balance between Angiopoietin-1 and -2 (Ang-1 and -2) is of particular importance [118] . In a multicenter cohort study, low plasma levels of Ang-1 at admission as well as serially measured Ang-1 and -2 were associated with higher 28-d mortality in critically ill patients with severe sepsis [119] . Additionally, in patients with suspected infection, elevated Ang-2 plasma levels were detected during the first hour after admission and correlated with the development of severe sepsis and a higher mortality [120] .…”
Section: Angiopoetin-1 Und -2mentioning
confidence: 99%
“…En cuanto a la Ang-2, se almacena en los cuerpos de WeibelPalade, de donde se libera para los procesos de desestabilización del endotelio por disrupción celular, antagonizando los efectos de la Ang-1 e incrementando la inflamación y la activación endotelial, con la consecuente pérdida de plasma y hemorragia (15,28). Se ha observado que las dos son relevantes en los procesos que desembocan en la gravedad de los pacientes en estado crítico, sin que hasta la fecha se hayan dilucidado completamente los mecanismos de dicha actividad (29). En cuanto a los demás reguladores endoteliales, se ha observado que en poblaciones heterogéneas (modelos animales y pacientes con dengue grave), algunos de ellos se han correlacionado con manifestaciones vasculares e inflamatorias, lo cual podría ser un campo de desarrollo de tratamientos farmacológicos (22,28).…”
Section: Discussionunclassified